DD-013 Drug supply chain: how to prevent out of stock due to industrial failure? retrospective study in the central pharmacy of a university hospital. (24th March 2015) - Malet, L; Delpech, L; Meunier, A; Derain, L; Locher, F
Abstract : Background: The central pharmacy orders 2, 100 different drugs from over 80 suppliers. Its main mission is to ensure the continuous delivery of drugs in care units. Backorders are daily verified in order to avoid out of stock situation. Purpose: The objectives are to identify classes of drugs most frequently impacted and to present an organisational pattern to prevent interruption in patient's treatment. Material and methods: We retrospectively analysed all stock-outs between January 2014 and September 2014 in the central pharmacy, based on warnings notes we sent to care units. We identified classes of drugs most frequently impacted, we listed the solution implemented in each case, then regarding to most suitable solution we built an organisational pattern to overcome out of stock. Results: During the study, 63 stock-outs occurred; 36% of stock-outs involved anti-infective agents, 21% involved nervous system drugs, remaining 43% equally affected 9 other classes of drugs. 5 different solutions were identified, ranked toward their pertinence and future place in the organisational pattern: 12% solved by changing primary packaging (volume, number of tablet in the package) 32% solved by a drug switch (princeps/generic) including 9% solved by an importation managed by national agency of medicines 18% solved by changing pharmaceutical form 18% solved by changing dosage 20% solved by a drug substitution (same ATC class) Conclusion: The study resulted in a classification of the solutions regarding their priority and the development of an organisational pattern to face efficiently future stock-outs. It's also important to get the information as soon as possible to act quickly. In fact, 11 stock-outs were notified on the national agency of medicines website. In this context, tracking orders and minimum stocks are very useful tools to prevent out of stock situation and discontinuity in patient treatment. References and/or acknowledgements: No conflict of interest.